DEVELOPMENT OF THE BANKING SECTOR OF UKRAINE IN THE CONDITIONS OF COMPETITIVE INTERNALIZATION: METHODICAL APPROACH TO EVALUATION - Diatlova , Yu.V. (The actual problems of regional economy development, 2020)
The modern development of the banking sector of Ukraine takes place in conditions of fierce competition of domestic banks with foreign banks, which actively use internalization tools as a competitive advantage in the Ukrainian financial market. The relevance of the study of such conditions for the development of the banking sector and the need to develop a methodical approach to their evaluation determined the purpose of this article. The research were used methods of statistical analysis (to determine trends in the development of the banking sector by certain indicators), mathematical modeling and calculation (to determine the level of competitive internalization and other indicators), logical generalization (to formulate results and conclusions). It was found that the indicators of the number of foreign banks present on the national market and their assets are insufficient to characterize the conditions of development of domestic banks. It was proposed to use the coefficient of competitive internalization. The methodical approach to assessing the development of the banking sector in a competitive internalization was improved using a set of static and dynamic indicators, which are used in combination or as separate and are determined for a country relative to another country or its bank for a year or other period. Calculations have shown that the influence of foreign banks on the banking sector of Ukraine can be compared with the banking sector of Moldova from the countries of the Commonwealth of Independent States, from the European Union member states – with the banking sector of Slovenia. The use of indicators in practice will allow forming information and statistical resource on the level of the banking sector development, in particular of banks with domestic capital, as well as to make decisions on the integration of the banking sector to other countries.